FLIGHT SCHEDULING SYSTEM DESIGN IN MANDALA AIRLANES - Amir Fauzi; Irwan Bastian, SKom, MM Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 1998)
Computerized information system is one way to achieve maximum service so that theprocessing of data to be effective and efficient. By conducting interviews withrelevant parties about the system is running, then the results were analyzed, thisresearch produced the conclusion that PT. Mandala Airlanes is in need of acomputerized information system to support operational activities, especially theflight scheduling problem.